Chemical peels: A review of current practice. (24th October 2017) - O'Connor, Alicia A; Lowe, Patricia M; Shumack, Stephen; Lim, Adrian C
Abstract: Chemical peels belong to a group of cutaneous resurfacing procedures that are used in the treatment of photoageing, inflammatory dermatoses, epidermal proliferations, pigmentary disorders and scarring. This review describes best current practice, highlights recent advances in chemical peel technology and discusses the recommended uses for different peel types. It also presents the results of a survey of the chemical peeling practices of 30 Australian dermatologists.